GE_GERICHTE P/5851/2013 vom 19. März 2014 - GE Cour de justice (2014)
PRISE D'OTAGES; CONTRAINTE(DROIT PÉNAL); COAUTEUR(DROIT PÉNAL); BRIGANDAGE; TENTATIVE(DROIT PÉNAL); DÉSISTEMENT(DROIT PÉNAL); FIXATION DE LA PEINE; PEINE COMPLÉMENTAIRE; SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | CP.185.1; CP.181; CP.140.1; CP.22.1; CP.23.1; CP.43